TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN FISIKA: KOMPUTERISASI EKSPERIMEN BUNYI BERBASIS SOUNDCARD LAPTOP - Ishafit, Ishafit (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Computerization experiments of sound based on laptop soundcard have been carried out. Topics of the experiment consists of measuring speed of sound in air with time of flight methods, visualization and measurement of the frequency of the sound beats phenomenon, measurement of the frequency spectrum of sound color (timbre), and measurement of sound frequency changes on the Doppler effect. The software used in this experiment is Audacity and overtones. Viewing from the experimental results and processes it can be obtained that the measurement processes including visual phenomenon of sounds is easy to do, and the measurement results have a high accuracy. Keywords: teknologi innformasi dan komunikasi, eksperimen bunyi, dan soundcard laptop.